Soil concentrations and source apportionment of polybrominated diphenyl ethers (PBDEs) and trace elements around a heavily industrialized area in Kocaeli, Turkey - Cetin, Banu (Springer Heidelberg, 2014)
Air pollutants are transported by dry deposition, wet deposition, and gas exchange accumulated in soil. Therefore, soil is an important environmental medium reflecting the level and the spatial distribution of air pollutants such as polybrominated diphenyl ethers (PBDEs) and heavy metals. Soil concentrations of seven PBDE congeners and 21 trace elements were determined in a heavily industrialized region (Dilovasi) in Kocaeli, Turkey. At all sites, Sigma 7PBDE concentrations ranged from 0.70 to 203 with a mean value of 26.3 mu g kg(-1) (dry weight). The congener profiles and mass inventories of PBDEs and their interactions with soil organic matter (SOM) were also investigated. BDE-209 was the dominant congener at all sites, followed by BDE-99 and/or -47. The estimated inventory of PBDEs for the Dilovasi district was 310 kg. However, there are several additional industrial regions in Kocaeli city. Considering the total land area, the potential inventory would be much larger for this city. The relationship between the PBDE concentrations in soil and SOM content indicated that factors other than soil properties have a greater influence on soil concentrations. Crustal enrichment factors (EFs) were determined; correlation analysis and factor analysis (FA) were also applied to generated data set to identify and apportion the sources polluting the soil. Sn, Mn, Ca, As, Zn, Pb, and Cd had significantly high average EF values, indicating that their soil concentrations were mainly influenced by anthropogenic activities. In FA, six factors were extracted with a cumulative variance of 84.4 % and industrial activities and traffic were found to be the main factors affecting the soil profile.
Keywords: PBDEs; Trace elements; Factor analysis; Enrichment factor; Mass inventory